2013
DOI: 10.1634/theoncologist.2012-0369
|View full text |Cite
|
Sign up to set email alerts
|

Trastuzumab for the Treatment of Salivary Duct Carcinoma

Abstract: Objectives. Salivary duct carcinoma (SDC) is a rare and aggressive malignancy with high mortality and poor response to treatment. A significant fraction of SDCs are HER2 positive. This retrospective review examines HER2 testing in SDC and the outcome of trastuzumab-based therapy in adjuvant and palliative settings. Methods. A total of 13 patients with SDC and HER2/neu expression by immunohistochemistry of 1-3ϩ were treated with trastuzumab in adjuvant (n ϭ 8) or palliative (n ϭ 5) setting. Adjuvant therapy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
137
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(144 citation statements)
references
References 29 publications
(34 reference statements)
4
137
1
1
Order By: Relevance
“…There are several reports of patients treated with androgen deprivation therapy, Trastuzumab and Venmurafinib for metastatic SDCa with partial to complete response [30][31][32][33][34][35]. However, these modalities have not been accepted as mainstream treatments for SDCa.…”
Section: Discussionmentioning
confidence: 99%
“…There are several reports of patients treated with androgen deprivation therapy, Trastuzumab and Venmurafinib for metastatic SDCa with partial to complete response [30][31][32][33][34][35]. However, these modalities have not been accepted as mainstream treatments for SDCa.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies of novel treatment strategies for SDC investigated the systemic use of molecularly targeted therapies (14)(15)(16)(35)(36)(37). Trastuzumab, which targets HER2, effectively prevents the recurrence of metastatic HER2-positive breast cancer.…”
Section: Sdc Was First Described In 1968 Bymentioning
confidence: 99%
“…SDC histologically resembles intraductal and infiltrating mammary duct carcinoma, and previous studies reported the therapeutic efficacy of adjuvant or palliative trastuzumab, carboplatin and paclitaxel for SDC, which frequently overexpresses HER2 (14-16,35-37). Limaye et al described 8 patients with HER2-positive SDC who were treated with concurrent radiation and chemotherapy consisting of weekly paclitaxel, carboplatin and trastuzumab after surgical resection, followed by adjuvant trastuzumab monotherapy (16). Of the patients who received adjuvant therapy, 38% experienced recurrence, but all patients with metastatic disease responded to treatment with trastuzumab.…”
Section: Sdc Was First Described In 1968 Bymentioning
confidence: 99%
See 2 more Smart Citations